2019
DOI: 10.1108/par-12-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Business tax to value-added tax reform in China

Abstract: Purpose This paper aims to examine the indirect tax reform process in China. Specifically, it examines the reform of business tax to value-added tax. Inefficiencies within the new tax system are identified and discussed. The “business tax to value-added tax” reform was seen as an essential element in promoting the economic transition and stimulating the service industries (Jin and Jin, 2013). Design/methodology/approach The paper uses archival and current literature. In undertaking the study, the different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…China’s taxation is mainly levied in value-added tax (VAT). The common belief is that VAT in the Chinese tax system can reduce the tax burden, improve production efficiency and market mechanisms, promote the service sectors, accomplish the economic transition and align with modernized and international practices (Wang et al , 2019). For domestic transactions using RMB, the taxation must impose on the capital gains of NFT and levy-related VAT, consumption tax and other taxation that may be involved.…”
Section: Resultsmentioning
confidence: 99%
“…China’s taxation is mainly levied in value-added tax (VAT). The common belief is that VAT in the Chinese tax system can reduce the tax burden, improve production efficiency and market mechanisms, promote the service sectors, accomplish the economic transition and align with modernized and international practices (Wang et al , 2019). For domestic transactions using RMB, the taxation must impose on the capital gains of NFT and levy-related VAT, consumption tax and other taxation that may be involved.…”
Section: Resultsmentioning
confidence: 99%
“…VAT has an important impact on economic development (Asllani and Statovci, 2018;Ayoub and Mukherjee, 2019;Huang et al, 2019;Wang et al, 2019). Hoseini and Briand (2020) found that the replacement of sales tax with VAT in India improved production efficiency.…”
Section: Introductionmentioning
confidence: 99%